Temperature evaluation of dental implant surface irradiated with high-power diode laser. Issue 7 (September 2016) - Rios, F.; Viana, E.; Ribeiro, G.; González, J.; Abelenda, A.; Peruzzo, D.
Abstract The prevalence of peri-implantitis and the absence of a standard approach for decontamination of the dental implant surface have led to searches for effective therapies. Since the source of diode lasers is portable, has reduced cost, and does not cause damage to the titanium surface of the implant, high-power diode lasers have been used for this purpose. The effect of laser irradiation on the implants is the elevation of the temperature surface. If this elevation exceeds 47 °C, the bone tissue is irreversibly damaged, so for a safety therapy, the laser parameters should be controlled. In this study, a diode laser of GaAsAl was used to irradiate titanium dental implants, for powers 1.32 to 2.64 W (real) or 2.00 to 4.00 W (nominal), in continuous/pulsed mode DC/AC, with exposure time of 5/10 s, with/without air flow for cooling. The elevation of the temperature was monitored in real time in two positions: cervical and apical. The best results for decontamination using a 968-nm diode laser were obtained for a power of 1.65 and 1.98 W (real) for 10 s, in DC or AC mode, with an air flow of 2.5 l/min. In our perspective in this article, we determine a suggested approach for decontamination of the dental implant surface using a 968-nm diode laser.